Pemberdayaan Berbasis Teknologi dan Informasi Melalui Aplikasi Maktabah Al Syamilah dan Maushuah Al Hadis di Pesantren Alhidayah Prapak Kranggan Kabupaten Temanggung Jawa Tengah - Moh. Syafi’; Ana Sofiyatul Azizah (Institut Islam Nahdlatul Ulama Temanggung, 2019)
This study is the result of the IT-based empowerment assistance with Maktabah Syamilah and Maktabah Mausu’ah al Hadits applications at Pesantren Alhidayah Prapak Kranggan, Temanggung. This Pesantren has not integrated the Technology and Information of digital library software and applications as part of the integral learning facilities at the Pesantren. The digital library applications (perpustakaan digital) of Maktabah Syamilah and Maktabah Mausu’ah al Hadits both provide convenience, efficiency, and accuracy in obtaining the reference for Islamic studies sources that are very easy to use for education at Pesantren Alhidayah. By employing the PAR (participatory action research), sociological, and phenomenological method, the Pesantren community has the following perception prior to the assistance program: first, the skepticism towards the Maktabah Syamilah and Mausu’ah al Hadits applications due to the Wahhabism indications. Second, the moderate views towards the Maktabah Syamilah and Mausu’ah al Hadits applications as the enrichment to the cross-sectarian Islamic thoughts. Meanwhile, after the assistance program, they succeeded in carrying out the transformative actions as follows. First, they show a skill to use and utilize the Maktabah Syamilah and Mausu’ah applications appropriately. Second, they are motivated for applying the Maktabah Syamilah and Mausu’ah as an integral part of the educational system. Third, they apply the Maktabah Syamilah and Mausu’ah into the learning system, Pesantren discussions, and Pesantren library. Forth, they are able to synchronize the contents of Maktabah Syamilah and Mausu’ah with the manual version.